Internal Control Mechanisms for Prevention of Accounting Errors and Frauds in Educational Institutions in Nepal - Rai, Harka Bir (DMC Journal, 2025)
This study aims to examine the prevalent internal control mechanisms in educational institutions and the impact in prevention of accounting errors and fraud. The data were gathered by 65 structured questionnaires from the head teacher, campus chief, accountants, teachers and auditors. The descriptive statistics were used to analyze the data. Hypotheses were formulated and tested based on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework. The relation among the five points of the COSO framework and the prevention of accounting fraud and errors was established by formulating a hypothesis. It was found that the majority of the public schools, compared to private and higher educational institutions (campuses), do not have a strict internal control policy. According to the study’s findings, the five components of the COSO framework have a positive correlation with the prevention of accounting fraud and errors. The study recommended that better implementation of an internal control system prevents fraud and decreases financial misconduct.